Impact of regulatory environment on accruals manipulation of bankrupt firms. Issue 1 (2nd January 2021) - Aldahray, Ayman; Alnori, Faisal
ABSTRACT: The aims of this study are twofold: first, to determine whether bankrupt firms manipulate signed accruals upwards compared with active firms with similar performance, and second, whether the regulatory environment influences pre-bankruptcy manipulation. Using the performance-matched discretionary accrual model and 500 firm-year observations, this study finds that bankrupt firms manipulate signed accruals upwards. Further, it examines subsamples of positive and negative accruals manipulation in the lightly regulated Alternative Investment Market (AIM) and the heavily regulated Main Market. Analysis of the first subsample reveals that bankrupt firms delisted from AIM manipulate accruals upwards more than bankrupt firms delisted from the Main Market. These results suggest that managers in bankrupt AIM firms have greater incentive and ability to manipulate accruals upwards compared with managers in Main Market firms. Finally, analysis of the negative accruals manipulation subsample shows that AIM bankrupt firms manipulate accruals downwards more than Main Market bankrupt firms.